THE INFLUENCE OF REGIONAL FINANCIAL MANAGEMENT, ACCOUNTABILITY AND TRANSPARENCY ON THE FINANCIAL PERFORMANCE OF THE MUNA DISTRICT GOVERNMENT - Asrya Asrya; Nining Asniar Ridza; La Ode Abdul Rakhman (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to examine and analyze the influence of regional financial management, accountability, and transparency on the financial performance of the Muna Regency Government. The research method used was a quantitative method with a survey approach. Primary data were obtained through the distribution of questionnaires to 105 respondents consisting of Regional Apparatus Organization (OPD) employees. Data analysis was carried out using the SPSS program through validity testing, reliability testing, descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, coefficient of determination, and statistical hypothesis testing. The results of the study indicate that: (1) regional financial management has a negative and significant effect on the financial performance of Muna Regency; (2) accountability has a negative and significant effect on the financial performance of Muna Regency; (3) transparency has a negative and significant effect on the financial performance of Muna Regency; and (4) simultaneously, regional financial management, accountability, and transparency have a negative and significant effect on the financial performance of the Muna Regency Government. These findings emphasize that the better the governance, information openness, and accountability implemented, the higher the regional financial performance achieved.